Gestión de riesgos ergonómicos en la actividad de acabados en la construcción de viviendas de la empresa LP ENGINEERING SOLUTIONS - Pomboza Guijarro, Andrés Alejandro (2022)
ABSTRACT: The aim of this work is to implement ergonomic risk prevention and control measures due to the postural conditions to which the workers of LP Engineering Solutions are exposed in the execution of the finishing construction activity. The postural conditions of the heaviest manual jobs that can generate occupational ailments related to the activities executed were identified. Through a direct observation method, the work cycles, the different angles formed by the workers´ limbs and the time that each worker remains in each posture were determined. For this purpose, photographs of different views were taken, it was possible to have a better perception of the angles formed by the members of the body in each executed activity and, through the tables applicable to the REBA (Rapid Entire Body Assessment) method, a score was assigned to each postural zone as indicated by the National Institute for Occupational Safety and Health (INSST). Once the risks to which the company's workers were exposed had been identified and evaluated, the different short- and long-term prevention and control measures were proposed. Proposing ergonomic recommendations and immediately applying the proposed prevention and control measures, an adequate execution of the activity was generated, with this the workplace was designed and the effectiveness of the proposed control measures was verified.